Effect of mechanical vibration sputum expectoration in the adjuvant treatment of stroke-associated pneumonia (机械振动排痰辅助治疗卒中相关性肺炎的效果观察) - LIU Wenli (刘文丽); CHEN Cheng (陈程); WANG Xin (王欣); PANG Xiaoyu (庞晓宇); ZHOU Dengfang (周登芳); GAO Jiajia (高佳佳) (中西医结合护理)
Objective To investigate the effect of mechanical vibration sputum expectoration in the adjuvant treatment of stroke-associated pneumonia. Methods Totally 60 patients with stroke-associated pneumonia were divided into control group (n=30)and study group(n=30) according to the arrival sequences of hospital admission. All patients received anti-infective therapy for stroke-associated pneumonia. The routine hand-assisted percussion on the back was adopted in the control group, while the mechanical vibration sputum expectoration was carried out in the study group. The clinical symptoms and clinical pulmonary infection scores of the two groups were observed at one week after intervention. Results The overall response rate of treatment was 96. 67%(29/30)in the study group, which was higher than 80. 00%(24/30)in the control group (P＜0. 05). Patients in the study group had a higher volume of sputum expectoration and shorter time to moist rale disappear compared with those in the control group (P＜0. 01). Patients in the study group achieved better outcomes of respiratory rate, SaO 2 and PaO 2 compared with those in the control group (P＜0. 01). Conclusion Application of mechanical vibration sputum expectoration is potentially effective to improve the condition of patients and enhance the treatment efficacy of stroke-associated pneumonia. (目的 探讨机械振动排痰辅助治疗卒中相关性肺炎的效果。方法 选取2019年 2 月—2020 年 8 月医院收治的脑卒中患者60例为研究对象, 均确诊卒中相关性肺炎。按患者入院时间顺序分为对照组和研究组, 各30例。2组患者均接受基础抗感染治疗, 对照组给予传统人工叩背手段排痰, 研究组给予机械振动排痰。1周后观察2组患者的临床症状和临床肺部感染评分。结果 研究组总有效率96. 67%(29/30), 高于对照组的80. 00%(24/30), 差异有统计学意义(P＜0. 05)。研究组排痰量多于对照组, 肺部湿啰音消失时间短于对照组, 差异有统计学意义(P＜0. 01)。研究组呼吸频率、血氧饱和度(SaO 2 )、动脉血氧分压(PaO 2 )改善幅度优于对照组, 差异有统计学意义(P＜0. 01)结论 运用机械振动排痰辅助治疗可以改善卒中相关性肺炎善患者肺部感染病情, 提高治疗效果。)